It's never too late for 'us' to meet 'them': prior intergroup friendships moderate the impact of later intergroup friendships in educational settings. - Al Ramiah, A; Hewstone, M; Voci, A; Cairns, E; Hughes, J (2013)
BACKGROUND: In this paper, we focused on mixing in educational settings between members of Catholic and Protestant ethnoreligious groups in Northern Ireland. AIMS: In Study 1, we examined whether opportunities for contact at home and at university were associated with greater actual out-group friendships, and whether this friendship was associated with a reduction in prejudice. We also assessed whether the impact of out-group friendships at university was moderated by experience of out-group friendships outside university, such that the prejudice-reducing effect of university friendships was stronger for those with fewer friendships at home. In Study 2, we assessed opportunities for contact and actual out-group friendships at prior stages of the educational system and their relationship with prejudice. Sample(s). In both studies, our participants were students at universities in Northern Ireland (Study 1 N= 304 and Study 2 N= 157). METHODS: We analysed the data using multiple regression and structural equation modelling. RESULTS: First, opportunities for contact were positively associated with self-reported out-group friendships in all domains and stages of the educational system. Second, having more out-group friends was associated with reduced prejudice. Finally, the relationship between out-group friendships and current levels of prejudice was moderated by prior levels of out-group friendships (at home in Study 1; and at secondary and primary school in Study 2). CONCLUSIONS: Contact, in the form of out-group friendships, was more powerful when it was a novel feature in a person's life. We discuss these findings in terms of the impact of mixing in educational contexts, especially in Northern Ireland, and outline suggestions for future research.